Fatigue in Loading and Unloading Workers at the Port (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
The port has a fairly dense loading/unloading activity according to the total flow of goods it manages. In addition to high work activities, environment factors such as noise and work climate can also affect the occurrence of work fatigue. Therefore, this study aims to determine factors associated with work fatigue in loading/unloading workers at the port. This study uses cross sectional study design with simple random sampling. Data analysis used the Paired Sample T-Test and Chi-Square test. The results showed that there was a difference of fatigue before and after work and as many as 71.2% of workers experienced moderate fatigue. It is known that age (p-value = 0,000), breakfast habits (p-value = 0,000), and years of service (p-value = 0,000) have a significant correlation with work fatigue, while nutritional status (p-value = 0.203), workload (p-value = 0.140), hot work climate (p-value = 0.362), and noise (p-value = 0.880) have no correlation with work fatigue. It was concluded that age, breakfast habits and work duration were related to work fatigue in loading/unloading labor. Therefore, workers are advised to be used to have breakfast with the right menu and time and workers should wear hats while working to reduce sun exposure.